1998
DOI: 10.1021/bi981128k
|View full text |Cite
|
Sign up to set email alerts
|

Membrane Topology of the Human Dipeptide Transporter, hPEPT1, Determined by Epitope Insertions

Abstract: We have used epitope insertion to analyze the transmembrane topology of the human H+-dipeptide symporter hPEPT1. An epitope tag, EYMPME (EE), was inserted into different locations at amino acids 39, 78, 106, 412, and 708 of hPEPT1 by site-directed mutagenesis. The functional integrity of the tagged protein was tested by measuring its dipeptide transport activity in transfected Cos7 cells. Further, cells expressing hPEPT1 or EE-tagged hPEPT1 derivatives were labeled with an anti-EE-monoclonal antibody (anti-EE-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
57
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
5
5

Relationship

3
7

Authors

Journals

citations
Cited by 74 publications
(61 citation statements)
references
References 22 publications
4
57
0
Order By: Relevance
“…Most of the POT members share a common structural architecture with ~12 predicted transmembrane domains (TMDs), but among the dipeptide transporters in distant phyla, variations on this theme do occur. We have confirmed the transmembrane topology of at least a portion of the main intestinal transporter, hPepT1, using an epitope tagging approach (12).…”
Section: Introductionmentioning
confidence: 61%
“…Most of the POT members share a common structural architecture with ~12 predicted transmembrane domains (TMDs), but among the dipeptide transporters in distant phyla, variations on this theme do occur. We have confirmed the transmembrane topology of at least a portion of the main intestinal transporter, hPepT1, using an epitope tagging approach (12).…”
Section: Introductionmentioning
confidence: 61%
“…Although mutations at the C/EBP sites markedly reduce transcriptional activity (Shiao et al 2000), we found no variations in this region in our test population. Among the four novel nonsynonymous polymorphisms, one, Gly419Ala in SLC15A1, was located in the large extracellular loop that carries potential N-glycosylation sites (Liang et al 1995;Covitz et al 1998). On the other hand, two polymorphisms in SLC22A1, Pro283Leu and Arg287Gly, were located in the intracellular loop that carries potential phosphorylation sites for protein kinase C (Zhang et al 1997).…”
Section: Resultsmentioning
confidence: 99%
“…In situ hybridization detects hPepT1 in the tip of mucosal cell villi but not in the crypts. The predicted protein has 708 amino acids with 12 transmembrane domains (7,8). This peptide transporter accepts dipeptides and tripeptides as its substrates, but it cannot transport free amino acids (9).…”
Section: Introductionmentioning
confidence: 99%